Управління розвитком персоналу на машинобудівних підприємствах України - Сисоліна, Н. П.; Нісфоян, С. С.; Sysolina, N.; Nisfoyan, S. (Аграрния университет, 2014)
Розглянуто системний підхід до управління розвитком персоналу, його трудового потенціалу на сучасних машинобудівних підприємствах. Приведено результати дослідження по оцінці ефективності витрат на утримання і розвиток персоналу підприємств. In the article аpproach of the systems is considered to the management development of personnel, him labour potential on modern machine-building enterprises. As a results of the implemented research an estimation of efficiency of charges on maintenance and development of personnel of enterprises.
Management development of personnel on the machine-building enterprises of Ukraine
Keywords: управління розвитком персоналу; інтелектуальний капітал; матриця якісної оцінки; management development of personnel; intellectual capital; matrix of high-quality estimation